Conservation status, sex and body size of reptiles in Santiago Nonualco, El Salvador - Pérez-García, José Nicolás (2023)
ABSTRACT. “Conservation status, sex and body size of reptiles in Santiago Nonualco,  El Salvador”. Introduction: In recent years, there has been an increase in the number of reptile species considered threatened by emerging pressures in El Salvador. Body characteristics are observable traits that help in the evaluation of their conservation status, but little has been done in El Salvador on this subject. Objective: To evaluate the conservation status, sex and body size of the reptiles of Santiago Nonualco, El Salvador. Methods: We compared the conservation status in official listings with the Environmental Vulnerability Index. Results: We identified 36 species, 14 in some conservation category, six threatened and one at risk of extinction in El Salvador. Individuals of medium body size and adults were the most abundant. Males were larger and more abundant, except in turtles. Conclusion: Santiago Nonualco provides refuge for several reptiles, including threatened species. Turtles differ from other reptiles in sexual differences; and small individuals were less frequently seen in this census.